Pengalaman Perawat dalam Memonitor Pasien Covid-19 - Masela, Victor Carlos; Kosasih, Cecep Eli; Emaliyawati, Etika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the experience of nurses in monitoring Coronavirus Disease 2019 (COVID-19) patients at Tantara Hospital, Ambon City. The method used is qualitative research using a phenomenological design. Participants in the study were health workers working in the isolation room, namely nurses with the following criteria: a minimum of 2 years work experience in the isolation room and a minimum diploma of three, fulfilling the qualifications as an isolation health worker and communicating cooperatively with researchers. Research data collection was carried out using semi-structured interviews, then analyzed using the Colaizzi analysis method. The results showed that there were 5 themes related to the experience of nurses in monitoring COVID-19 patients: Anxiety, Knowledge, nurse loyalty, nurses' feelings, and efforts to reduce the risk of contracting it. In conclusion, nurses experience anxiety due to high job demands, including long working hours, nurse knowledge, loyalty, nurses' feelings and efforts to reduce the risk of infection are very important for nurses to be able to provide appropriate nursing care for patients. Keywords: COVID-19, Emergency, Intensive care unit